RELATIONSHIP OF FAMILY SUPPORT WITH INDEPENDENCE OF SELF-CARE IN MENTAL RETARDATION IN SLB TN II MANCAR VILLAGE, PETERONGAN DISTRICT - Rosita, Yoga; Puspita Aryani, Hany; Puspita, Sylvie (PRIMA WIYATA HEALTH, 2020)
The development of children who experience mental retardation will have an influence on the ability of children and the involvement of children to function in the environment. Children are not able to be independent as individuals who are able to carry out their own daily activities (motoric), limitations in understanding social behavior and the development of social skills. This study aims to determine the relationship of family support with self-care independence in mentally retarded children at SLB TN II in Mancar village, Peterongan District, Jombang Regency. This study uses the Correlational Quantitative Analytical approach. The sample technique used was total sampling, namely all mentally retarded children at SLB TN II in Mancar village, Peterongan District, Jombang Regency, 24 people. Data collection uses a questionnaire to measure family support and independence of self-care of children. Chi Square data analysis and contingency coefficient. Based on the results of the analysis obtained the value of p = 0,000 (p <0.05), meaning that there is a relationship between family support and self-care independence in mentally retarded children at SLB TN II in Mancar village, Peterongan District, Jombang Regency with the strength of relationships in sufficient categories. Parents are expected to be able to provide support as needed by mentally retarded children to increase their independence in self-care.